DEFORESTASI PANTAI TIMUR SUMATRA DALAM NOVEL BERPACU NASIB DI KEBUN KARET, KULI, DAN DOEKOEN KARYA MADELON SZEKELY-LULOFS - Sudibyo, Sudibyo (Balai Bahasa Jawa Timur, 2014)
The Novels Berpacu Nasib di Kebun Karet, Kuli, and Doekoen by Szekely?Lulofs written on the basis of author's involvement in plantation companies on the East Coast of Sumatra, represents the world of a plantation with all of its characteristics. Through Berpacu Nasib di Kebun Karet, Kuli, and Doekoen, Szekely-Lulofs delivers reportage on the deforestation of the Sumatran East Coast being converted to plantation lands and the growth of plantation companies in Deli and its surrounding areas in the 1930s. Exploitation of forest resources was largely carried out by the Dutch and other foreign companies which secured concessions from the Dutch Colonial Government. This study attempts to explain the ecological transformation of the Sumatran East Coast in the form of deforestation and conversion of the new land as plantation, describes the practices of dehumanization against the plantation workers as the excesses of the achievement of certain economic targets, describes the new lifestyle of the planters as the impact of economic growth occurred in the area. To achieve that goals, the researcher conducts close and contrapuntal reading to expose the ecological colonialism practice. The theory used are postcolonial ecology based on the assumption that colonialism does not only change the structure of social, political, and cultural of colonized society but also radically changes the ecology and traditional livelihood patternsThe Novels Berpacu Nasib di Kebun Karet, Kuli, and Doekoen by Szekely-?Lulofs written on the basis of author's involvement in plantation companies on the East Coast of Sumatra, represents the world of a plantation with all of its characteristics. Through Berpacu Nasib di Kebun Karet, Kuli, and Doekoen, Szekely-Lulofs delivers reportage on the deforestation of the Sumatran East Coast being converted to plantation lands and the growth of plantation companies in Deli and its surrounding areas in the 1930s. Exploitation of forest resources was largely carried out by the Dutch and other foreign companies which secured concessions from the Dutch Colonial Government. This study attempts to explain the ecological transformation of the Sumatran East Coast in the form of deforestation and conversion of the new land as plantation, describes the practices of dehumanization against the plantation workers as the excesses of the achievement of certain economic targets, describes the new lifestyle of the planters as the impact of economic growth occurred in the area. To achieve that goals, the researcher conducts close and contrapuntal reading to expose the ecological colonialism practice. The theory used are postcolonial ecology based on the assumption that colonialism does not only change the structure of social, political, and cultural of colonized society but also radically changes the ecology and traditional livelihood patterns Key Words: deforestation; transformation; ecology; exploitation; dehumanization Abstrak: Novel Berpacu Nasib di Kebun Karet, Kuli, dan Doekoen karya Szekely-Lulofs yang ditulis berdasarkan keterlibatan pengarang di perusahaan perkebunan di Pantai Timur Sumatra merepresentasikan dunia perkebunan dengan segala karakteristiknya. Melalui Berpacu Nasib di Kebun Karet, Kuli, dan Doekoen, Szekely?Lulofs menyampaikan reportase tentang deforestasi Pantai Timur Sumatra yang dikonversikan sebagai lahan perkebunan dan pertumbuhan perusahaan perkebunan di Deli dan sekitarnya pada tahun 1930?an. Eksploitasi sumber daya hutan ini sebagian besar dilakukan oleh perusahaan Belanda dan perusahaan asing lain yang mendapatkan konsesi dari Pemerintah Kolonial Belanda. Penelitian ini berupaya untuk menjelaskan transformasi ekologi berupa deforestasi Pantai Timur Sumatra dan konversi lahan baru itu sebagai lahan perkebunan; menjelaskan praktik dehumanisasi terhadap para pekerja perkebunan sebagai ekses dari pencapaian target ekonomi tertentu; menjelaskan gaya hidup baru dari para pekebun sebagai dampak dari pertumbuhan ekonomi yang terjadi di daerah itu. Untuk mencapai tujuan itu dilakukan pembacaan dekat (close reading) dan teknik pembacaan kontrapuntal (contrapuntal reading) untuk menyingkap praktik kolonialisme ekologis itu. Adapun teori yang digunakan adalah teori ekologi pascakolonial yang bertolak dari asumsi bahwa kolonialisme tidak hanya mengubah struktur sosial, politis, dan kultural masyarakat terjajah, tetapi juga secara radikal mengubah ekologi dan pola?pola penghidupan tradisional.